COMPETENCIES FOR TEACHER LIBRARIANS IN MALAYSIA - Haji Abdullah, Abrizah (Malaysian Journal of Library and Information Science, 1999)
The study identifies the role of teacher librarians in secondary schools as perceived by three groups of people directly involved in school librarianship - teacher librarians, library educators and education officers. The study also determines the essential competencies and the type of education required by teacher librarians to perform their role. A Likert-type questionnaire comprising 10 role statements, 61 competency statements and 9 personal competency statements was mailed to three groups of 20 teacher librarians, library educators and education officers. The ratings given identify the roles and competencies considered essential. Based on the C.O.T.E standards, 17 out of the 61 proposed competencies were considered essential by at least 51% of the survey respondents. The study also identifies areas for future planning in the training and education of teacher librarians in Malaysia.